Pemberdayaan remaja putri melalui edukasi sadari sebagai deteksi dini kanker payudara - Lutfi, Sofia; Maulina, Rufidah (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Breast cancer remains a major health concern and one of the top causes of mortality among women in Indonesia. Breast Self-Examination (BSE), or SADARI, is a simple yet vital method for early detection. This study aimed to determine the effectiveness of leaflet-based education in increasing adolescent girls’ understanding of SADARI. The program was conducted in Dusun Glagah Kidul RT 02, Klaten, involving 30 female participants aged 10 to 20 years. The intervention included interactive educational sessions and hands-on demonstrations using a breast model, with knowledge assessed through pre- and post-tests. Data analysis employed the Wilcoxon Signed-Rank test due to non-normal data distribution. Findings revealed an increase in average test scores from 7.70 (pre-test) to 9.27 (post-test), with a significance level of p = 0.000. This indicates a statistically significant improvement in knowledge following the intervention. Leaflet-based education proves to be an effective strategy for raising awareness of early breast cancer detection among adolescent girls.